Kemampuan Mahasiswa dalam Menerapkan Fungsi-Fungsi Manajemen di Sekolah - Sartika, Didi (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2022)
Abstract : The essential thing that prospective MPI graduates must possess is to understand the functions of management and the development of concepts. Management functions are basic elements that are always attached and used as references by a manager in carrying out the management process to achieve efficient and effective goals and required professional skills and can be ratified into 4 (four) management functions which are abbreviated to (POAC) namely Planning, Organizing, Actuating and Controlling. Initial identification of prospective graduates of MPI IAIN Takengon still lacks in understanding and implementing management functions in the world of work. This research is categorized as the quantitative research method. The research was conducted by distributing questionnaires to students who had completed PPL 1 and PPL 2 courses. The results showed that the percentage of prospective graduates of MPI IAIN Takengon in implementing management functions was at a good level. This is evident from the ability to implement the planning function as much as 70%, organizing as much as 71%, implementing or directing as 69%, and controlling as 70%. The total score of students' abilities in all management functions is 70%.Keyword: Work Ability, Management Functions